Members of the Chromobox Family Have Prognostic Value in Hepatocellular Carcinoma - Pan, Chenxi; Luo, Nan; Guo, Kun; Wang, Wenbo; Li, Lei; Fan, Ning; Tian, Yu (Frontiers in Genetics, 2022)
Liver cancer is the fifth most prevalent malignant tumor, while hepatocellular carcinoma represents the most prevalent subtype worldwide. Previous studies have associated the chromobox family, critical components of epigenetic regulatory complexes, with development of many malignancies owing to their role in inhibiting differentiation and promoting proliferation of cancer cells. However, little is known regarding their function in development and progression of hepatocellular carcinoma. In the present study, we analyzed differential expression, prognostic value, immune cell infiltration, and gene pathway enrichment of chromobox family in hepatocellular carcinoma patients. Next, we performed Pearson's correlation analysis to determine the relationships between chromobox family proteins with tumor-immune infiltration. Results revealed that high expression of CBX1, CBX2, CBX3, CBX6, and CBX8 was associated with poor survival rates of hepatocellular carcinoma patients. These five factors were used to build prognostic gene models using LASSO Cox regression analysis. Results indicated that high expression of CBX2 and CBX3 proteins was significantly associated with poor prognosis for hepatocellular carcinoma patients. The resulting nomogram revealed that CBX3 and T stages were significantly correlated with prognosis of hepatocellular carcinoma patients. Notably, predictive CBX3 was strongly correlated with immune cell infiltration. Furthermore, results from functional enrichment analysis revealed that CBX3 was mainly involved in regulation of methylation of Histone H3-K27. Collectively, these findings suggest that CBX3 could be a biomarker for predicting prognosis of hepatocellular carcinoma patients.